Analisis Kinerja Laporan Keuangan Menggunakan Metode Economic Value Added Pada Perusahaan Go Public - Salsa Safhira; Dedi Darwis (Jurnal Ilmiah Sistem Informasi Akuntansi, 2021)
In attracting the attention of these investors, the company must be able to show good company financial performance, because investors will only be interested in investing or buying shares in companies with good financial performance. The part that is most analyzed by investors to find out the condition of a company is through financial statements, because financial statements can describe the condition of a company whether or not the company's finances are good or not. Economic Value Added (EVA) is a measure to measure the performance of financial statements that best describes the company's Economic Profit when compared to other measures. In addition, Economic Value Added (EVA) is a measure that is closely related to the prosperity of shareholders over time. The application of Economic Value Added (EVA) in a company can also focus more on creating company value, this is one of the advantages of Economic Value Added (EVA). By using this approach, shareholders or investors can see how much added value the company achieves each year. The test results from this design process can be concluded that the web-based system of Financial Statement Performance Analysis Using the Economic Value Added Method in Go Public Companies can be used to analyze the company's financial condition in the positive (0), negative (0) or break-even (=0) categories. ) as a decision-making material for potential investors before investing in a company.